Impact of martial arts (Judo, Karate, and Kung Fu) on bone mineral density gains in adolescents of both genders: 9-month follow-up - Ito, Igor H. [UNESP]; Kemper, Han C.G.; Agostinete, Ricardo R. [UNESP]; Lynch, Kyle R. [UNESP]; Christofaro, Diego G.D. [UNESP]; Ronque, Enio R.; Fernandes, Rômulo A. [UNESP] (Human Kinetics, 2017)
Purpose: To compare bone mineral density (BMD) gains in adolescents of both genders stratified according to different martial art styles in a 9-month follow-up study. Methods: The longitudinal study consisted of 29 adolescents of both genders and age between 11 and 17 years stratified into a control group (not engaged in any sport) and 50 fighters (kung fu/karate, n = 29; judo, n = 21). All 79 subjects underwent anthropometric measures (weight, height, leg length, and height set) and dual-energy X-ray absorptiometry (BMD, in g/cm2) at 2 moments, baseline and 9 months later. Maturity offset (age at peak height velocity), lean soft tissue, chronological age, and resistance training were treated as covariates. Results: Male judoists presented higher gains in BMD-spine [0.098 g/cm2 (95% confidence interval, 0.068–0.128)] than control group [0.040 g/cm2 (95% confidence interval, 0.011–0.069)] (post hoc test with P = .030). There was no effect of martial art on BMD gains among girls. Independently of gender, in all multivariate models, lean soft tissue constituted the most relevant covariate. Conclusions: Judo practice in adolescents affected the bone accrual significantly after 9-month follow-up compared with controls, mainly in boys.
Keywords: Bone health; Combat sports; Pediatric population; Youth